Odpowiedź :
Odpowiedź:
[tex]a)\\\\(5-x)(x+8)(2x-6)=0\\\\5-x=0\ \ \ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x+8=0\ \ \ \ \vee\ \ \ \ 2x-6=0\\\\-x=-5\ \ |\cdot(-1)\ \ \ \ \vee\ \ \ \ x=-8\ \ \ \ \ \ \vee\ \ \ \ 2x=6\ \ |:2\\\\x=5\ \ \ \ \ \ \ \ \ \vee\ \ \ \ \ \ x=-8\ \ \ \ \ \ \ \ \vee\ \ \ \ x=3[/tex]
[tex]b)\\\\(3-x)(x+6)(2x-8)=0\\\\3-x=0\ \ \ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x+6=0\ \ \ \ \vee\ \ \ \ 2x-8=0\\\\-x=-3\ \ |\cdot(-1)\ \ \ \ \vee\ \ \ \ x=-6\ \ \ \ \vee\ \ \ \ 2x=8\ \ |:2\\\\x=3\ \ \ \ \ \ \ \ \vee\ \ \ \ \ \ \ \ x=-6\ \ \ \ \ \ \ \ \vee\ \ \ \ x=4[/tex]
Odpowiedź:
[tex](5 - x)(x +8)(2x - 6) = 0\\\\1.5-x=0|+5=x=5\\2.x+8=0|-8=x=-8\\3.2x-6=0|+6=x=3\\\\x^{1}=5\\x^{2}=-8\\x^{3}=3[/tex]
[tex](3 - x)(x + 6)(2x - 8) =0\\\\3-x=0|+3=x=3\\x+6=0|-6=x=-6\\2x-8=0|+8=x=4\\\\x^{1}=3\\x^{2}=-6\\x^{3}=4[/tex]
Mam nadzieję że pomogłam, miłego wieczoru!